ILUMINAÇÃO NATURAL EM AMBIENTE ASSOCIADO A VARANDA COM PEITORIL EM VIDRO - Mapelli, Yulli Ribeiro; Laranja, Andréa Coelho; Alvarez, Cristina Engel de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The research aims to define a natural environment according to the variation of the opening area, associated with a balcony with glass sill. As simulations were performed with the TropLux software of a pre-determined environment of the city of Vitória-ES (LAT 20 ° 19'S), in the CIE standards types 3, 7 and 12 in the North, South, East and West orientations. The ambient light values are compared to the UDI value ranges. Uses five models of doors associated with a balcony with glass sill. The points of view were equidistant in an orthogonal mesh of 0.75m height of the floor on days and days pre-established. It is concluded that the upper door models are superior to 50% of the facade area, in all orientations, provide the results of the results for sky 7 (overcast) and sky 12 (clear). It should also be noted that port P4 (about 66% of the area in relation to the façade) when oriented north presents percentages of hours framed th artificial lighting.